The Role of Ultrafiltration in Patients with Decompensated Heart Failure - Sandeep A. Kamath (International Journal of Nephrology)
Congestion, due in large part to hypervolemia, is the primary driver of heart failure (HF) admissions. Relief of congestion has been traditionally achieved through the use of loop diuretics, but there is increasing concern that these agents, particularly at high doses, may be deleterious in the inpatient setting. In addition, patients with HF and the cardiorenal syndrome (CRS) have diminished response to loop diuretics, making these agents less effective at relieving congestion. Ultrafiltration, a mechanical volume removal strategy, has demonstrated promise in achieving safe and effective volume removal in patients with cardiorenal syndrome and diuretic refractoriness. This paper outlines the rationale for ultrafiltration in CRS and the available evidence regarding its use in patients with HF. At present, the utility of ultrafiltration is restricted to selected populations, but a greater understanding of how this technology impacts HF and CRS may expand its use.